Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù‚ØµØ© Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© ÙÙŠ Ø¨Ù†Ø§Ø¡ Ø§Ù„Ø´Ø®ØµÙŠØ© Ø§Ù„ÙØªØ§Ø© Ø§Ù„Ù…Ø³Ù„Ù…Ø© Ù‚ØµØ© Ù…Ø±ÙŠÙ… -Ø¹Ù„ÙŠÙ‡Ø§ Ø§Ù„Ø³Ù„Ø§Ù…- Ù†Ù…ÙˆØ°Ø¬Ø§ - Syarifah Naadhiya (Universitas Darussalam Gontor, 2023)
This study discusses the story in the Qur'an in building the character of Muslim women based on the story of Maryam ‘alaihassalam to be a role model, example, and method in their lives. This story is to reform the corrupted condition of society and to show the purpose of the Qur'an and the highest values raised for society. The researcher thought to discuss and discover the current deviation of Muslim women clarifying the features of the Qur'anic approach to the story of Maryam ‘alaihassalam and how to treat it. The researcher used inductive and descriptive analysis methods to design Qur'anic methodology to solve the problem. The researcher has achieved important results through the research, namely the strength of Maryam's ‘alaihassalam unification in her worship of Allah Subhanahu wa Ta’ala. She maintained her chastity and sought refuge in Allah Subhanahu wa Ta’ala when a strange man came to her, even though it was the angel Jibril, and was content with Allah's decree when the lord of Allah Subhanahu wa Ta’ala chose her to conceive without being touched by humans. This is one of the purposes of the Qur'an, telling the story of Maryam ‘alaihassalam in her worship and praiseworthy qualities as she emulates Muslim women in building the perfect modern women personality.